RANCANG BANGUN ALAT PENJERNIH AIR BERBASIS BACKWASH MENGGUNAKAN METODE QUALITY FUNCTION DEPLOYMENT (QFD) - Faradila Ananda Yul; Denur Denur (Jurnal Teknik Industri Terintegrasi, 2021)
Clean water is one of the necessities that must be fulfilled for the continuity of life. This research was conducted in Pekanbaru at the Nuansa Kulim Indah Housing Community Type 36. This research was conducted to design, build and calculate the cost of a-based water purifier backwash. The method is Quality Function Deployment used to obtain a comfortable design for residential communities. For designing-based water purifier backwash an ergonomic, the dimensions of the-based water purifier are backwash adjusted to the anthropometry of the Nuansa Kulim Indah housing community with data on upright height (TBT) 165.10 cm, forward hand reach (JTD) 68.88 cm and length arm arm (PLT) 73.27 cm. The based water purifier is backwash -equipped with pressure pressure to identify the state of the filter media so that the filter media is kept clean. In addition, the-based water purifier is backwash designed for cleaning by reversing the direction of the water (backwash) if theprocess is backwash no longer possible to clean the filter media because the dirt content has clumped up and cannot be pushed with the water pressure itself, then the flange fitting provided can opened for manual cleaning.